(untitled) (The Journal of Plant Protection Sciences, 2023)
Ganoderma which was identified to have antifungal potential by dual culture technique against sheath blight pathogen of rice was developed as an emulsifiable concentrate. The formulation of 10EC at 0.25% was standardized as the best emulsifiable concentration for use against the pathogen. The pre inoculation spray of the formulation was observed to produce 63.62% reduction in lesion height caused by the sheath blight pathogen. Two isoforms of poly phenol oxidase, PPO 1 and PPO 3 were observed to be induced only in Ganosol 10EC sprayed plants and were absent in control. The formulation was tested to have good emulsion stability. The antifungal activity of the formu lation persisted up to seven days after spraying the formulation on rice plants. The formulation retained its 100% antifungal efficacy up to three months of storage. Surprisingly, spraying cowpea plants with the formulation as simultaneous spray reduced the number of lesions produced by Groundnut Bud Necrosis virus in cowpea by 88.39% when compared to the inoculated control, suggesting the antiviral potential of the formulation.